Co valence transformation in isopolar LaCo O3/LaTi O3 perovskite heterostructures via interfacial engineering - Araizi-Kanoutas G.; Geessinck J.; Gauquelin N.; Smit S.; Verbeek X.H.; Mishra S.K.; Bencok P.; Schlueter C.; Lee T.-L.; Krishnan D.; Fatermans J.; Verbeeck J.; Rijnders G.; Koster G.; Golden M.S. (My University, 2025)
We report charge transfer up to a single electron per interfacial unit cell across nonpolar heterointerfaces from the Mott insulator LaTiO3 to the charge transfer insulator LaCoO3. In high-quality bi- and trilayer systems grown using pulsed laser deposition, soft x-ray absorption, dichroism, and scanning transmission electron microscopy-electron energy loss spectroscopy are used to probe the cobalt-3d electron count and provide an element-specific investigation of the magnetic properties. The experiments show the cobalt valence conversion is active within 3 unit cells of the heterointerface, and able to generate full conversion to 3d7 divalent Co, which displays a paramagnetic ground state. The number of LaTiO3/LaCoO3 interfaces, the thickness of an additional, electronically insulating "break" layer between the LaTiO3 and LaCoO3, and the LaCoO3 film thickness itself in trilayers provide a trio of control knobs for average charge of the cobalt ions in LaCoO3, illustrating the efficacy of O-2p band alignment as a guiding principle for property design in complex oxide heterointerfaces. © 2020 American Physical Society.